Identifikasi Lesbian dan Dikotomi Butch pada Tokoh Kishimoto Ruka dalam Serial Drama Last Friends Karya Kato Hiromasa, Nishisaka Mizuki dan Endo Mitsutaka - VALENTINE, RIZKI HAKIKI (Jurnal Ilmiah Mahasiswa FIB, 2013)
Homosexuality is a controversial theme that is often adapted into fiction, so that, film industries publicate it as television serials. This research used a Japanese serial entitled ‘Last Friends’ as the main data. Last Friends tells us about a lesbian named Kishimoto Ruka who loves a straight girl. This research’s result shows things that identificates Kishimoto Ruka as a butch lesbian. This research uses gender and sexual orientation theory. The butch dicothomy that is representated by Kishimoto Ruka was analysed based on Levitt and Hiestand’s butch and femme sexuality development’s table. Besides, mise en scene was also used to help explaining the story, strengthen the emotions of the serials. The result shows that there are lesbian identity and butch dicothomy in Kishimoto Ruka which is representated through her masculine performances and attitudes, the way she treated, protected and sacrificed her self for someone she really loved; Michiru. Kishimoto Ruka also rejects woman’s gender roles and her dialog representates danseigo characteristic which is often used by male. Kishimoto Ruka’s dialog implies that she isn’t interested in man, but woman. Her love for Aida Michiru is showed through her sacrificing, jealousy, and physical contacts that indicates her erotic emotions towards Michiru. This Japanese serial can be inspected with different topics such as; Gender Identity Disorder (GID) girl’s psychological condition that is reflected in Kishimoto Ruka, woman masculinity that is reflected in Kishimoto Ruka, domestic violence and Oikawa Sosuke’s jealousy response, and psychological research towards Aida Michiru as a domestic violence’s victim. Keywords: drama, lesbian, butch, woman, sexual orientation, gender.